2012
DOI: 10.1038/ajh.2012.116
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Central Aortic Pulse Pressure: Noninvasive Brachial Cuff-Based Estimation by a Transfer Function Vs. a Novel Pulse Wave Analysis Method

Abstract: Large random and systematic errors are introduced into the PP-C estimates when PP-C is calculated as the difference between the estimated central SBP and central or cuff DBP. The accuracy can be improved substantially with the novel PWA approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Lack of consistency among Table 1. The stability validation of the periodic output of an artificial pulse generator system using the mean harmonic components ( cn ) and intra-class correlation coefficient, ICC (2,1 The p-value assesses the statistical significance of the null hypothesis that there is no correlation between five measurements (H 0 : ICC(2,1) ¼ 0); CI, confidence internal. Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of consistency among Table 1. The stability validation of the periodic output of an artificial pulse generator system using the mean harmonic components ( cn ) and intra-class correlation coefficient, ICC (2,1 The p-value assesses the statistical significance of the null hypothesis that there is no correlation between five measurements (H 0 : ICC(2,1) ¼ 0); CI, confidence internal. Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…The generalized transfer function (GTF), pulse wave velocity (PWV), augmentation index (AI) and harmonic analysis (HA) have been used to assess central aortic pressure [1], arterial stiffness [2] and other cardiovascular diseases [3].…”
Section: Introductionmentioning
confidence: 99%
“…The patient characteristics and study procedures are described in detail elsewhere [10], [11]. Information relevant to the present study is briefly described below.…”
Section: Methodsmentioning
confidence: 99%
“…PWA is more specific for the individual patient than the method using GTF for estimating CBP [25]. The GTF is based on population average and does not take into account individual characteristics such as age, gender, and disease status.…”
Section: Pulse Wave Analysis Versus Gtfmentioning
confidence: 99%
“…In addition, some GTF-based devices calculate cPP by subtracting cuff DBP from cSBP because clinical evidence showed that central DBP does not significantly differ from peripheral DBP [19]. However, calculating cPP this way appears to be less accurate than the directly assessed cPP by means of PWA as the GTF-based method bears measurement errors for both cuff SBP and DBP [25]. …”
Section: Pulse Wave Analysis Versus Gtfmentioning
confidence: 99%